Determinación de materia orgánica y oxígeno disuelto en el Río Jubones sector La Iberia - Arévalo Niebla, Mirella J. (2007)
Contamination is impregnation of the air, the water or the floor with products that affect to the man´s health, the quality of life or the natural operation of the ecosystems. The presence of big quantities of water is what distinguishes to the earth of the other well-known planets and that makes here possible the life. The rivers are important for that provide water and nutrients for agriculture, inhabit for diverse flora and fauna, as well as routes for the trade, recreation and electricity. The rivers have been used as drains for the waste of the agriculture and of the industry.